Resepsi Hadis-hadis Nafkah dalam Media Sosial: Studi terhadap Konten Youtube @FaqihAbdulKodir - Mohammad Fauzan Ni'ami; Umi Sumbulah; Moh. Irfan (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
This empirical-ethnographic research delves into the burgeoning landscape of social media discussions, particularly focusing on the YouTube channel @FaqihAbdulKodir. Amidst the plethora of content, this channel stands out for its unique exploration of ḥadīth through the lens of qirā’ah mubādalah, attracting a substantial audience and gaining recognition among academics and gender activists. Employing reception theory analysis, this study seeks to synthesize insights from @FaqihAbdulKodir’s exploration of ḥadīth concerning livelihood. The research sheds light on the reception of the prophet’s teachings, unraveling the intricate process of knowledge transmission. The findings reveal a spectrum of internalisations, rooted in the understanding of reciprocity. The research concludes with three distinct types of reception. First, an exegesis reception manifests as a trending interpretation style of living ḥadīth. Second, an aesthetic reception highlights the beauty of Islamic teachings, fostering equality before God, particularly in matters of livelihood. Third, a functional reception emerges, emphasizing mutuality in family income as a cornerstone for household harmony. This study not only contributes to the academic discourse on ḥadīth but also offers insights into the multifaceted impacts of @FaqihAbdulKodir’s channel on individuals’ perceptions and practices in their daily lives.